2003
DOI: 10.1037/0022-3514.85.6.1193
|View full text |Cite
|
Sign up to set email alerts
|

To Do or to Have? That Is the Question.

Abstract: Do experiences make people happier than material possessions? In two surveys, respondents from various demographic groups indicated that experiential purchases-those made with the primary intention of acquiring a life experience--made them happier than material purchases. In a follow-up laboratory experiment, participants experienced more positive feelings after pondering an experiential purchase than after pondering a material purchase. In another experiment, participants were more likely to anticipate that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

32
953
4
30

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 852 publications
(1,048 citation statements)
references
References 26 publications
32
953
4
30
Order By: Relevance
“…", and "how much does mobile internet contribute to your happiness in life?" [4], [22] Usage frequency ranges from "very often" (scored 1, over five hours a day) to "never used it" (scored 6). Usage variety was measured following the same approach as the Wi-Fi Adoption and Security Survey 2012 Hong Kong [11].…”
Section: Methodsmentioning
confidence: 99%
“…", and "how much does mobile internet contribute to your happiness in life?" [4], [22] Usage frequency ranges from "very often" (scored 1, over five hours a day) to "never used it" (scored 6). Usage variety was measured following the same approach as the Wi-Fi Adoption and Security Survey 2012 Hong Kong [11].…”
Section: Methodsmentioning
confidence: 99%
“…These results consequently supported the idea that money can buy happiness if it is spent right (Dunn, Gilbert, & Wilson, 2011;Dunn & Norton, 2013). One of the main findings was that spending money on experiences rather than on material goods makes people happier (Van Boven, 2005;Van Boven & Gilovich, 2003).The studies mentioned above used similar experimental designs. Typically, a small sample of university students were randomly assigned into two groups, and members of one group were asked to think about the most recent experiential purchase they made, and members of the other group were asked to think about the most recent material purchase they made.…”
mentioning
confidence: 99%
“…Thomas and Millar (2013) found that experiential purchases had more impact on the self than material purchases, and they showed that this impact mediated the relationship between purchase type and subjective well-being. This characteristic of experiential purchases can also explain why we more often avoid unfavorable comparisons of experiences and why memories of experiential but not material purchases may become more positive over time (Carter & Gilovich, 2010).Experiences also have an inherent social nature (Van Boven & Gilovich, 2003); they are typically experienced with others, whereas material goods are more often enjoyed alone.1 For a detailed review see Gilovich and Kumar (2015 Finally, people adapt more quickly to material goods than experiences. Nicolao, Irwin, and Goodman (2009) examined the adaptation process after material and experiential purchases over a two-week period.…”
mentioning
confidence: 99%
See 2 more Smart Citations